Pengelolaan Dana Bantuan Operasional Sekolah Dalam Peningkatan Mutu Pendidikan SD Di Labakkang Kabupaten Pangkep - Syamsul Bakhtiar Ass; Mustafa Mustafa; Henidar Juana; Kherayani Nur; Abdurrahman Hadi (Institute Agama Islam Negeri (IAIN) Sultan Amai Gorontalo, 2024)
This research was carried out at the Elementary School (SD) Labakkang District, Pagkep Regency. The aim of this research is to determine the impact of managing School Operational Assistance (BOS) funds on improving the quality of elementary school education in Labakkang District, Pangkep Regency.The data analysis method used in this research is a quantitative method. The sample in the research was 80 respondents, while the sampling technique in the research used simple random sampling. To answer the hypothesis, instrument tests are used, consisting of validity tests and reliability tests. The regression test consists of simple regression analysis, correlation coefficient test (R) and determination coefficient test (R2). Test the hypothesis using a partial test (t test). All analysis methods were processed using the SPSS version 25 program.